Evidence of depot‐specific regulation of all‐trans‐retinoic acid biosynthesis in human adipose tissue - Katya B. Rubinow; Guo Zhong; Lindsay C. Czuba; Judy Y. Chen; Estell Williams; Zoe Parr; Saurabh Khandelwal; Daniel Kim; Jeffrey LaFrance; Nina Isoherranen (Wiley, 2022)
Abstract The prevalence of obesity continues to rise, underscoring the need to better understand the pathways mediating adipose tissue (AT) expansion. All‐trans‐retinoic acid (atRA), a bioactive vitamin A metabolite, regulates adipogenesis and energy metabolism, and, in rodent studies, aberrant vitamin A metabolism appears a key facet of metabolic dysregulation. The relevance of these findings to human disease is unknown, as are the specific enzymes implicated in vitamin A metabolism within human AT. We hypothesized that in human AT, family 1A aldehyde dehydrogenase (ALDH1A) enzymes contribute to atRA biosynthesis in a depot‐specific manner. To test this hypothesis, parallel samples of subcutaneous and omental AT from participants (n = 15) were collected during elective abdominal surgeries to quantify atRA biosynthesis and key atRA synthesizing enzymes. ALDH1A1 was the most abundant ALDH1A isoform in both AT depots with expression approximately twofold higher in omental than subcutaneous AT. ALDH1A2 was detected only in omental AT. Formation velocity of atRA was approximately threefold higher (p = 0.0001) in omental AT (9.8 [7.6, 11.2]) pmol/min/mg) than subcutaneous AT (3.2 [2.1, 4.0] pmol/min/mg) and correlated with ALDH1A2 expression in omental AT (β‐coefficient = 3.07, p = 0.0007) and with ALDH1A1 expression in subcutaneous AT (β‐coefficient = 0.13, p = 0.003). Despite a positive correlation between body mass index (BMI) and omental ALDH1A1 protein expression (Spearman r = 0.65, p = 0.01), BMI did not correlate with atRA formation. Our findings suggest that ALDH1A2 is the primary mediator of atRA formation in omental AT, whereas ALDH1A1 is the principal atRA‐synthesizing enzyme in subcutaneous AT. These data highlight AT depot as a critical variable for defining the roles of retinoids in human AT biology.